The hidden and complex relationship between dietary phosphorus and malnutrition in hemodialysis patients with chronic kidney disease - Milla Clonia; Widodo; Wardhana Teddy Heri (Romanian Journal of Internal Medicine, 2024)
Chronic kidney disease (CKD) has always been a complicated global challenge, ranking as the 12th leading cause of death worldwide. Hemodialysis, being one of the most opted renal replacement therapies (RRTs) for patients with end-stage renal disease (ESRD), still possesses some limitations in preventing complications, such as malnutrition and mineral bone disease (CKD-MBD). While efforts have focused on controlling CKD-MBD parameters like calcium and phosphate, less attention has been given to dietary interventions. Moreover, the adoption of low-phosphorus diets for hemodialysis patients is very complex due to potential conflicts with the guideline-recommended high-protein dietary approach. This study sought to investigate the relationship between dietary phosphorus intake and nutritional status in CKD patients undergoing regular hemodialysis.